A discrete-continuous optimization approach for the design and operation of synchromodal transportation networks - Resat, H. Giray; Turkay, Metin (Computers & industrial engineering, 2019)
•Modeling mixed-integer linear and non-linear optimization problem.•Using ∊–constraint method for solving multi-objective problem.•Integrating specific characteristics of synchromodal transportation in novel models.•Generating Pareto solutions for transportation decision makers in real-life cases. This paper presents a multi-objective mixed-integer programming problem for integrating specific characteristics of synchromodal transportation. The problem includes different objective functions including total transportation cost, travel time and CO2 emissions while optimizing the proposed network structure. Traffic congestion, time-dependent vehicle speeds and vehicle filling ratios are considered and computational results for different illustrative cases are presented with real data from the Marmara Region of Turkey. The defined non-linear model is converted into linear form and solved by using a customized implementation of the ∊-constraint method. Then, the sensitivity analysis of proposed mathematical models with pre-processing constraints is summarized for decision makers.